I tornado negli USA: un'analisi dell'archivio dati (1950-2018) - Sergio Pinna (Bollettino della Società Geografica Italiana)
A statistical analysis of the data contained in the NOAA’s Storm Prediction Center tornado archive (covering the period 1950-2018) has been carried out. The actual average values of the frequencies for the various intensity classes could be effectively provided for the period 1991-2018, because of some inhomogeneities of the archive due to variations in the methods and procedures of tornado reporting. The time series of the frequency of F2, F3, F4 and F5 events showed decreasing trends; this decline seems largely due to a significant reduction of the strongest events. This interpretation is supported by the decreasing trends of normalized economic losses and of number of victims.